Nutritional Content Analysis Of Yellow Pumpkin Brownies (Cucurbita Moschata L.) With Stevia Sweetener (Stevia Rebaudiana) As A Sugar Cane Substitution - Putri, Faizah Rahma; Aji, Arif Sabta; Salfarino, Ryan; Haidiyanti, Julistin; Nurjanah, Raudah (Ikatan Sarjana Gizi Indonesia (ISAGI), 2024)
An unhealthy diet that includes sugary snacks may promote a rise in glucose levels and enhance the risk of Type 2 Diabetes Mellitus (T2DM). Brownies are high in sugar and should be replaced with healthier ingredients to reduce their sugar content and glycemic index with stevia as natural sweeteners and yellow pumpkin which are low in calories and carbohydrates. To determine the nutritional content of brownies products with the substitution of cane sugar with stevia and yellow pumpkin. This study utilized a quasi-experimental design using completely randomized design (CRD). We experimented to evaluate the effects of four different treatments, comparing the use of cane sugar and stevia in different ratios: 100% cane sugar (P0), 50% cane sugar and 50% stevia (P1), 25% cane sugar and 75% stevia (P2), and 100% stevia (P3). Moisture, ash, protein, fat, carbohydrate and energy variables were tested using by different method, gravimetric, kjehdahl, soxhlet, by difference, and atwater which was repeated 3 times. We conducted data analysis using a one-way ANOVA and Duncan test to determine the treatment pairs with the highest significance level. The findings demonstrated that replacing cane sugar with stevia significantly affect the nutritional content of yellow pumpkin brownies products (p<0.05, for all comparisons). The treatments with the highest average of nutritional contents were as follows: P3 had the highest moisture content (48.64±0.04%), ash content (1.06±0.06%), protein (6.93±0.11%), and fat (14.49±0.34%), whereas P0 had the highest carbohydrate content (39.45±0.23%) and total energy (281.19±0.76 kcal/100g). The nutritional content of yellow pumpkin brownies has significantly modified by substituting sugar cane with stevia. However, additional investigation is required to determine other nutritional contents and assess its potential as functional food.